Taxonomic dissimilarity in patterns of interception and establishment of alien arthropods, nematodes and pathogens affecting woody plants in Europe. Issue 1 (9th October 2014) - Eschen, René; Roques, Alain; Santini, Alberto
Abstract: Aim: The number and impact of alien tree pests and pathogens increase in many countries as a result of international trade, despite phytosanitary measures aimed at preventing their introduction. We compared patterns in interceptions and establishments of alien arthropod pests and pathogens of woody plants in Europe. Location: European Union. Methods: Establishment data were extracted from the DAISIE and FORTHREATS databases and updated. Interception records (1995–2010) were obtained from the European and Mediterranean Plant Protection Organisation. Results: The rate of establishment increased, independently of host plant type, whether the species in the host genus are tropical or temperate, or whether invertebrates or pathogens, but interceptions were made on few host genera. There were large differences in the identities of the intercepted and established pests on species level, but similarities on higher taxonomic levels for arthropods and pathogens. Main Conclusions: Differences between interceptions and establishments may result from the inspection focus on regulated organisms; while most established species were never regulated and especially pathogens are hard to detect. We suggest using molecular techniques to detect pathogens in asymptomatic plants and that pest risk analysis target potentially harmful organisms at a higher taxonomic level to cover more, potentially unknown pests in groups that have become established.